(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article considers the ways of marketing activities in industrial enterprises and ways to further develop the marketing strategy carried out in the enterprise, at the same time, ways to increase the income of the enterprise.